Novel solute carrier family 26, member 3 mutation in a prenatal recurrent case with congenital chloride diarrhea - Wu, Siqi; Han, Jin; Zhang, Yongling; Ye, Zhichao; Lu, Ping; Tian, Kege (The journal of obstetrics and gynaecology research, 2019)
Congenital chloride diarrhea (CCD) is an autosomal recessive hereditary disease manifested by persistent, watery, profuse diarrhea with high chloride concentration (>90 mmol/L). Postnatally, neonates suffer from hypochloremia, hyponatremia, hypokalemia, metabolic alkalosis, dehydration, developmental retardation, or even death. Prenatal diagnosis is of great importance for the prognosis of CCD. We report a prenatal recurrent case of CCD. Prenatal ultrasound revealed fetal diffuse intestinal dilation with the typical honeycomb sign and polyhydramnios with high amniotic fluid index. The whole exome capture and massively‐parallel DNA sequencing showed an abnormal mutation of Solute Carrier Family 26, Member 3 (SLC26A3), c.1039G>A (p.Ala347Thr), and the mutation sites were verified by sanger sequencing. When prenatal ultrasound shows polyhydramnios and diffuse intestinal dilation, CCD should be suspected. Molecular genetic testing can be helpful for the diagnosis.